The impacts of visual input on the quality of consecutive interpreting = Tác động của yếu tố đầu vào hình ảnh lên chất lượng dịch ứng đoạn - Kiều, Ngọc Anh (ĐHQGHN - Trường Đại học Ngoại ngữ, 2020)
The conditions in which interpreters work have long been recognized as being among the major factors determining the quality of the interpretation. As being among the determining objective factors, visual input in interpreting has thus been extensively researched. However, these are mostly in the field of simultaneous interpreting, while the measuring impacts of visual input on consecutive interpreting has received improper attention. This reason urged the researcher to choose visual input as an experimental tool to test its effects on the quality of consecutive interpreting, as well as the benefits and also difficulties it may bring to interpreters. The research obtained its data from a structured experiment and interview, from which a conclusion was drawn that the presence of visual input facilitated the improvement of quality in consecutive interpreting, along with the discovery of some advantages and disadvantages of having or not having visual input in the interpreting process as perceived by the interpreters.